Integrating Sustainability into Cosmetic Manufacturing and Consumption: Challenges and Innovations - Putriana Rachmawati; Sharon Susanto; Yulius Evan Christian (Universitas Katolik Indonesia Atma Jaya, 2025)
The global cosmetic industry continues to grow rapidly, with revenues projected to exceed USD 800 billion by 2030. However, the use of synthetic ingredients, plastic packaging, and energy- and water-intensive production processes has led to environmental impacts. This study examines the environmental impacts of the cosmetic industry through four key aspects: cosmetic ingredients, packaging, manufacturing processes, and consumer behavior. A literature review of publications from 2000 to 2025 obtained from major scientific databases was used. The results show that ingredients such as parabens, triclosan, and 1,4-dioxane contribute to pollution and environmental toxicity, while plastic packaging remains the main source of MPF. Sustainable alternatives, such as sugarcane straw extract, olive oil, whey protein isolate, and PLA-, cellulose-, and chitosan-based packaging materials, show strong potential to reduce environmental impact. Meanwhile, the adoption of renewable energy, waterloo systems, and recycling technologies in factories improves efficiency and reduces carbon emissions. Changes in consumer behavior, particularly among Generation Z, who are highly concerned about sustainability, also encourage producers to act more socially and environmentally responsibly. This study emphasizes the importance of implementing sustainable cosmetic practices to maintain a balance between industrial growth and environmental preservation.